HeartMate 3: new challenges in ventricular tachycardia ablation - Nof, Eyal; Peichl, Petr; Stojadinovic, Predrag; Arceluz, Martin; Maury, Philippe; Katz, Moshe; Tedrow, Usha B; Singh, Robin M; Narui, Ryohsuke; John, Roy M; Stevenson, William G; Beinart, Roy; et al. (Europace, 2022)
AIM: To describe clinical characteristics, procedural details, specific challenges, and outcomes in patients with HeartMate3TM (HM3), a left ventricular assist device system with a magnetically levitated pump, undergoing ventricular tachycardia ablation (VTA). METHODS AND RESULTS: Data were collected from patients with an HM3 system who underwent VTA in seven tertiary centres. Data included baseline patient characteristics, procedural data, mortality, and arrhythmia-free survival. The study cohort included 19 patients with cardiomyopathy presenting with ventricular tachycardia (VT) (53% with VT storm). Ventricular tachycardias were induced in 89% of patients and a total of 41 VTs were observed. Severe electromagnetic interference was present on the surface electrocardiogram. Hence, VT localization required analysis of intra-cardiac signals or the use of filter in the 40-20 Hz range. The large house pump HM3 design obscured the cannula inflow and therefore multi imaging modalities were necessary to avoid catheter entrapment in the cannula. A total of 32 VTs were mapped and were successfully ablated (31% to the anterior wall, 38% to the septum and only 9% to the inflow cannula region). Non-inducibility of any VT was reached in 11 patients (58%). Over a follow-up of 429 (interquartile range 101-692) days, 5 (26%) patients underwent a redo VT ablation due to recurrent VTA and 2 (11%) patients died. CONCLUSIONS: Ventricular tachycardia ablation in patients with HM3 is feasible and safe when done in the appropriate setup. Long-term arrhythmia-free survival is acceptable but not well predicted by non-inducibility at the end of the procedure.
Keywords: výsledek terapie; Recurrence; podpůrné srdeční systémy; Treatment Outcome; Heart-Assist Devices; lidé; katetrizační ablace; Catheter Ablation; kardiomyopatie; Humans; komorová tachykardie; Cardiomyopathies; Tachycardia, Ventricular; recidiva